P PENERAPAN SISTEM INFORMASI JALAN RAYA DALAM MENEGAKKAN BUDAYA DISIPLIN BANGSA - Teguh Arujisaputra, Erwin; Rachman, Andy Nur (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
Highways are among the worst communication environments. Various incidents that indicate communication failure always occur. Highways are indeed not designed as communication spaces, but communication symbols are scattered. It takes understanding and a mature attitude from communicators and communicants because they communicate more predominantly using nonverbal communication. The goal is to understand the symbols that appear through vehicles. However, communication will turn bad when the other party misinterprets the symbol. Egotistical-subjective assumptions arise that provoke emotions until physical fights inevitably occur. In this regard, this study aims to determine the factors that change the perception of road users to cause communication failure. Using qualitative methods with descriptive analysis types to reveal the facts that occur. The results of the study indicate that negative communication occurs because the ability to control road users is loose and unable to avoid it when brought to an emotional atmosphere. Meanwhile, negative communication in the form of curses or dirty words is included in the vocabulary of words in the emotional mental scope.